Analisis Multiplier Effect Sebagai Dampak Ekonomi dari Sumbawa Car Free Day - Putri Septihan Melinda; Rozzy Aprirachman (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study aims to analyze the direct, indirect, and subsequent impacts of Car Free Day (CFD) activities in Labuhan Badas Sub-district, Sumbawa Regency. The approach used is Multiplier Effect Analysis, which utilizes multiple effects based on real conditions in the field. In addition, this study also evaluates the perceptions of the community, labor, and businesses towards CFD activities with Descriptive Statistical Analysis, specifically through the Chi-Square Test. The data used is primary data, obtained through direct interviews with relevant respondents. With primary data collection and qualitative analysis, multiplier effect calculations can be performed. The results of the Multiplier Effect analysis show that the Keynesian Income Multiplier is 2.43, which means that every additional public expenditure of one rupiah can increase income by around 2.43 rupiah. In addition, the Income Multiplier Ratio of 1.06 indicates that every investment of one rupiah in CFD-related business units will result in an increase in income of 1.06 rupiah, including both direct and indirect impacts. Based on these results, the Multiplier Effect Analysis of CFD in Sumbawa Regency succeeded in achieving the research objectives, namely knowing the impact of Car Free Day activities on the local economy.